Simulation of vertical greenery system in reducing energy cooling loads for high rise residential building / Hazril Sherney Basher...[et al.] - Basher, Hazril Sherney; Sh. Ahmad, Sabarinah; Abdul Rahman, Abdul Rahman (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The Vertical Greenery System (VGS) is considered an alternative solution of passive shading that implements green wall to various type of building facades. The main contributions of this paper are that by installing the VGS, it will minimize the energy used to cool the indoor space and eventually save the energy cooling load by 7.6 percent for low rise condition and 18.27 percent for high rise. This is due to capability of VGS to reduce heat transfer to and from building envelope. The VGS used in this paper consisted of an edible legume plant which is 'Psophocarpus Tetrogonobulus' (Winged Bean Plant). This paper presents a series of recent simulation findings that uses Integrated Environmental Solutions Software (IESVE). The measured data were taken from the use of simulation models that comprised of Test Cell Unit (low rise) and Condo Unit (high rise). From the data, the VGS also managed to reduce the indoor air temperature by an average of 0.47°C for low rise unit and 1.53°C drop for high rise. These promising results indicated that the software was able to give an indication and prediction of annual energy savings through the benefits of shading. This effective strategy may improve the ambient temperature conditions in urban cities that experience excessive urban heat island due to overgrowth development and overpopulation.